Environmental Factors in the Etiology of Mental Disorders in the Czech Republic: Final Results - Hosak L; Hurdova K; Hrnciarova J; Zapletalova J; Koncelikova D; Latalova K (Neuropsychiatric Disease and Treatment)
Ladislav Hosak,1 Kristyna Hurdova,1 Jela Hrnciarova,1 Jana Zapletalova,2 Dana Koncelikova,3 Klara Latalova3 1Department of Psychiatry, University Hospital Hradec Kralove and Charles University, Faculty of Medicine in Hradec Kralove, Hradec Kralove, Czech Republic; 2Department of Medical Biophysics, Palacky University Olomouc, Faculty of Medicine and Dentistry, Olomouc, Czech Republic; 3Department of Psychiatry, University Hospital Olomouc and Faculty of Medicine and Dentistry, Palacky University Olomouc, Olomouc, Czech RepublicCorrespondence: Ladislav Hosak, Department of Psychiatry, University Hospital, Sokolska 581, Hradec Kralove, 500 05, Czech Republic, Tel +420 495 833 478, Fax +420 495 833 041, Email hosak@lfhk.cuni.cz